Analisis QOS Jaringan Internet ITK dengan Metode Hierarchical Token Bucket - Abdullah, Riska Kurnianto; Wibowo, Satrio Putra; Fiqar, Tegar Palyus (STMIK Banjarbaru, 2024)
Kalimantan Institute of Technology (ITK) is a state university in Balikpapan City, East Kalimantan. The quality of the internet network in ITK is not adequate, and this research analyzes Quality of Services (QoS) with the Hierarchical Token Bucket (HTB) method. The test results show that the average value of throughput on download is 853 Kbps (good), there is an increase of 7.8%, packet loss is not very influential, delay is 7.7 ms (very good), there is a very significant decrease in download delay of 31.6%, and jitter is 2,109 ms (bad), not too middle. HTB is good enough to improve QoS, especially on throughput and delay on the download channel on the ITK Network. The HTB method technically helps with the distribution of structured bandwidth management, reducing failures and delays in data delivery. This research shows that HTB can improve the quality of network services at ITK. The results of QoS measurements, such as throughput, packet loss, delay, and jitter, can be a reference for UPT TIK ITK to improve the quality of network services.Keywords: Quality of Service; Bandwidth Management; Network; Hierarchical Token Bucket Â AbstrakInstitut Teknologi Kalimantan (ITK) adalah perguruan tinggi negeri di Kota Balikpapan, Kalimantan Timur. Kualitas jaringan internet di ITK belum memadai, dan penelitian ini menganalisis Quality of Services (QoS) dengan metode Hierarchical Token Bucket (HTB). Hasil uji coba menunjukkan bahwa nilai rata-rata Throughput pada download adalah 853 Kbps (bagus) terjadi peningkatan 7.8%, Packet Loss tidak terlalu berpengaruh, Delay 7,7 ms (sangat bagus) terjadi penurunan yang sangat signifikan pada delay download yaitu 31.6%, dan Jitter 2.109 ms (jelek) belum terlalu berpengaruh. HTB cukup baik untuk meningkatkan QoS, terutama pada Throughput, dan Delay pada kanal download di Jaringan ITK. Metode HTB secara teknis membantu pembagian manajemen bandwidth yang terstruktur, mengurangi kegagalan dan keterlambatan pengiriman data. Penelitian ini menunjukkan bahwa HTB dapat meningkatkan kualitas layanan jaringan di ITK. Hasil pengukuran QoS, seperti throughput, packet loss, delay, dan jitter ini, dapat menjadi acuan UPT TIK ITK untuk meningkatkan kualitas layanan jaringan.Kata kunci: Quality of Services; Manajemen Bandwidth; Jaringan; Hierarchical Token BucketÂ